Agarose/spherical activated carbon composite gels for recyclable and shape-configurable electrodes - Kim, Jong Sik; Kim, Ju Hyung; Cho, Younghyun; Shim, Tae Soup (Polymers, 2019)
Soft electrodes have been known as a key component in the engineering of flexible, wearable, and implantable energy-saving or powering devices. As environmental issues are emerging, the increase of electronic wastes due to the short replacement cycle of electronic products has become problematic. To address this issue, development of eco-friendly and recyclable materials is important, but has not yet been fully investigated. In this study, we demonstrated hydrogel-based electrode materials composed of agarose and spherical activated carbon (agar/SAC) that are easy to shape and recycle. Versatile engineering processes were applied thanks to the reversible gelation of the agarose matrix which enables the design of soft electrodes into various shapes such as thin films with structural hierarchy, microfibers, and even three-dimensional structures. The reversible sol-gel transition characteristics of the agar matrix enables the retrieval of materials and subsequent re-configuration into different shapes and structures. The electrical properties of the agar/SAC composite gels were controlled by gel compositions and ionic strength in the gel matrix. Finally, the composite gel was cut and re-contacted, forming conformal contact to show immediate restoration of the conductivity.
Keywords: Activated carbon composites; Agarose; Engineering process; Environmental issues; Sol-gel transitions; Spherical activated carbons; Structural hierarchies; Three-dimensional structure; Activated carbon; Agarose; Conducting polymers; Hydrogels; Soft electrodes